A Comparative Review Of Conventional And Microwave Assisted Extraction In Capsaicin Isolation From Chili Pepper - Nour, A. H.; Olalere, Olusegun Abayomi (AENSI Publishing, 2016)
In recent times, major concern had been placed on the economic importance of major constituents of chili pepper to oursociety; research work had therefore been extensively carried out on the conventional way of extracting this active component called capsaicin obtainable in different cultivars of locally grown peppers. However several drawbacks abound when isolating capsaicin using the conventional approach and these include high solvent consumption, low extraction yield, solvent contamination, higher cost of extraction and longer extraction time, among other factors. These set therefore necessitated the introduction of an improved method called microwave assisted extraction. This review therefore provided a simple theoretical background tocapsaicin leaching processusing different traditional methods witha careful comparativedescription of microwave potential for optimum extraction.